"Your Ticket to Dreamsville": The Functions of 16 Magazine in American Girl Culture of the 1960s - (:unkn) unknown (My University, 2014)
This analysis reveals the ways in which 16 Magazine functioned in 1960s American girl culture, largely due to the influence of Gloria Stavers, the magazine's editor. Stavers used the features in 16 Magazine to become an emulous mother who guided her readers through their private fantasy space, or "Dreamsville," as well as the Cold War culture of the 1960s. 16 Magazine, the most popular youth culture magazine of the 1960s, incorporated dominant ideologies of Cold War anxieties and presented them in subtle, yet effective ways. Profiles of pop music and television stars, advice columns, beauty features, gossip columns, and "Your Ticket to Dreamsville" contests encouraged normative gender and consumer behavior for girls, yet broadened the definitions of "appropriate" behavior and style by incorporating countercultural signifiers, while the language throughout the magazine merged youth lingo with discourses of American patriotism. This project also reveals how the relationships between 16 Magazine and youth-oriented television programs functioned as entertainment narratives and models for the negotiations between the public and private spheres during the Cold War era and served as predecessors to contemporary cross-media texts, yet indicate their unique nature as non-corporate transmedia narratives, dependent upon fan participation and interaction while predating new media options for interactivity. This dissertation draws upon historical, cultural, and media theories, including those of Cold War domesticity, youth and girl culture, and transmedia convergence. The interdisciplinary analysis included herein is the first scholarly research that utilizes 16 Magazine as its primary source material.
Keywords: 16 Magazine; Girl Culture; Gloria Stavers; Magazines; Popular Music; Television